Regions, emotions and left-behindness: a phase model for understanding the emergence of regional embitterment - Hannemann, Matthias; Hennig, Sebastian; Schäfer, Susann (Regional studies, 2024)
Discontent is an important feature of ‘left-behind places’, often reflected by a high percentage of voting for populist parties. Drawing on insights from psychology, we extend previous analyses by focusing on collective embitterment as the central underlying emotional state in a region. Arguing that such negative emotions do not arise ‘out of the blue’, we develop a four-phase model of regional embitterment that accounts for the emotional characterisation of and the level of embitterment among the population, as well as the role of policy interventions. Based on a case study in East Thuringia, we conclude that emotions should be given more attention in future studies.